Dystocia frequency and causes in horses with pregnancy disorders or a history of dystocia: A prospective study - Ellerbrock, Markus; Krohn, Judith; Büttner, Kathrin; Wehrend, Axel; Justus Liebig University Giessen (My University, 2024)
Dystocia typically presents a life-threatening condition for both the mare and the foal. This prospective long-term study aimed to ascertain whether mares with prior pregnancy disorders or a history of dystocia were at a higher risk of experiencing subsequent dystocia in comparison to those without such medical antecedents. To achieve this goal, the authors analysed 207 parturitions and 164 mares over a 10-year period. Of these, 57 were associated with pregnancy disorders or prior dystocia (Group 1), while 150 parturitions followed uneventful pregnancies in mares that had not yet experienced dystocia (Group 2). Mares in Group 1 were significantly more likely to develop dystocia than those in Group 2 (p = .0180; odds ratio = 2.98). Foetal causes of dystocia were more prevalent than maternal causes (p < .0389). Maternal mortality stood at 0.5%, and neonatal mortality reached 1.9%. The results demonstrate that mares are at significantly higher risk of developing dystocia after experiencing pregnancy disorders or parturition complications during previous pregnancies, emphasizing the need for systematic birth monitoring.
Keywords: ddc:630